THE INFLUENCE OF STUDENT MANAGEMENT ON PSYCHOLOGICAL WELL BEING - Masruroh, Durrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
One of the problems in education that has a considerable influence is depression in students. Whether it is due to personal problems in the family or unpleasant school experiences, it can also be a source of stress and reduce students' quality of life at school and in their home environment. This study examines the "Influence of student management on psychological well-being" using quantitative research methods of ordinal data types with a correlative Associative quantitative approach. Researchers use data collection techniques with questionnaires to fill in all respondents in the last semester of MPI, as many as 55. Then the questionnaire results are input into Microsoft excel and SPSS 16 to find out whether the data is valid. A prerequisite test is carried out first to determine the feasibility of the data before Somer'S D analysis is carried out to determine whether student management influences psychological well-being. The results showed a significant influence between student management on psychological well-being, as evidenced by Approx. Sig. is less than the calculated value of 0.000 < of 0.05.